2015
DOI: 10.1002/jcp.25184
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Loading Stimulates Expression of Collagen Cross‐Linking Associated Enzymes in Periodontal Ligament

Abstract: Type I collagen, a major extracellular component of the periodontal ligament (PDL), is post-translationally modified by a series of specific enzymes. Among the collagen-modifying enzymes, lysyl oxidase (LOX) is essential to initiate collagen cross-linking and lysyl hydroxylases (LHs) to regulate the cross-linking pathways that are important for tissue specific mechanical properties. The purpose of this study was to investigate the effects of mechanical loading on the expression of collagen-modifying enzymes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 45 publications
3
36
0
Order By: Relevance
“…However, cartilage and ligament collagen show normal hydroxylation of telopeptide lysine and normal crosslinking patterns [57,58]. In line with this observation, it has recently been reported that the expression of LH2 increases in response to mechanical loading on the bone-associated, but not the cementum-associated, side of the periodontal ligament [53]. FKBP65, a peptidyl-prolyl cis-trans isomerase, is essential for the dimerization and enzymatic activity of LH2.…”
Section: Post-translational Modifications Of Type I Collagensupporting
confidence: 52%
See 2 more Smart Citations
“…However, cartilage and ligament collagen show normal hydroxylation of telopeptide lysine and normal crosslinking patterns [57,58]. In line with this observation, it has recently been reported that the expression of LH2 increases in response to mechanical loading on the bone-associated, but not the cementum-associated, side of the periodontal ligament [53]. FKBP65, a peptidyl-prolyl cis-trans isomerase, is essential for the dimerization and enzymatic activity of LH2.…”
Section: Post-translational Modifications Of Type I Collagensupporting
confidence: 52%
“…A number of unique collagen-modifying enzymes and molecular chaperones are involved in these processes [46,47]. Various factors affect post-translational modifications of type I collagen, including aging [48], systemic diseases (e.g., osteoporosis, osteopetrosis, OI, and diabetes) [32,49], and mechanical stress [50][51][52][53][54].…”
Section: Post-translational Modifications Of Type I Collagenmentioning
confidence: 99%
See 1 more Smart Citation
“…We also visualized collagen fibers by picrosirius red staining (Kaku et al, 2016). No overt changes were found in both E18.5 and P9 samples (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Type I collagen production is epigenetically controlled in PDL, with collagen expression decreasing with age . Furthermore, PDL‐derived cells have been shown to up‐ and downregulate various genes under mechanical stress . It is unknown whether the lack of prolyl 3‐hydroxylation in PDL is the result of low P3H2 gene expression or if the rapid turnover of collagen substrate potentially encumbers enzyme activity.…”
Section: Discussionmentioning
confidence: 99%